Editor's Choice – Assessment of Correlation Between Mean Size of Infrarenal Abdominal Aortic Aneurysm at Time of Intact Repair Against Repair and Rupture Rate in Nine Countries. (June 2020) - Grima, Matthew J.; Behrendt, Christian-Alexander; Vidal-Diez, Alberto; Altreuther, Martin; Björck, Martin; Boyle, Jonathan R.; Eldrup, Nikolaj; Karthikesalingam, Alan; Khashram, Manar; Loftus, Ian; Schermerhorn, Marc; Setacci, Carlo; et al.
Abstract : Objective: This study aimed to analyse the mean abdominal aortic aneurysm (AAA) diameter for repair in nine countries, and to determine variation in mean AAA diameter for elective AAA repair and its relationship to rupture AAA repair rates and aneurysm related mortality in corresponding populations. Methods: Data on intact (iAAA) and ruptured infrarenal AAA (rAAA) repair for the years 2010–2012 were collected from Denmark, England, Finland, Germany, Hungary, New Zealand, Norway, Sweden, and the USA. The rate of iAAA repair and rAAA per 100 000 inhabitants above 59 years old, mean AAA diameter for iAAA repair and rAAA repair, and the national rates of rAAA were assessed. National cause of death statistics were used to estimate aneurysm related mortality. Direct standardisation methods were applied to the national mortality data. Logistic regression and analysis of variance model adjustments were made for age groups, sex, and year. Results: There was a variation in the mean diameter of iAAA repair ( n  = 34 566; range Germany = 57 mm, Denmark = 68 mm). The standardised iAAA repair rate per 100000 inhabitants varied from 10.4 (Hungary) to 66.5 (Norway), p <.01, and the standardised rAAA repair rate per 100 000 from 5.8 (USA) to 16.9 (England), p <.01. Overall, there was no significant correlation between mean diameter of iAAA repair and standardised iAAA rate ( r 2 = 0.04, p = .3). There was no significant correlation between rAAA repair rate ( n  = 12 628) with mean diameter of iAAA repair ( r 2 = 0.2, p = .1). Conclusion: Despite recommendations from learned society guidelines, data indicate variations in mean diameter for AAA repair. There was no significant correlation between mean diameter of AAA repair and rates of iAAA repair and rAAA repair. These analyses are subject to differences in disease prevalence, uncertainties in rupture rates, validations of vascular registries, causes of death and registrations.